The Influence of the Wagner Group on Regional Security in the Sahel Region - Jemlak , Michael Mashal; Momoh, Zekeri (Kashere Journal of Politics and International Relations, 2025)
The Wagner Group, a Russian paramilitary organization, has increasingly influenced the security dynamics of the Sahel region, where weak governance, terrorism, and inter-communal conflicts persist. This study examines the influence of Wagner’s presence on regional stability, focusing on its role in counterterrorism operations, regime protection, and resource exploitation in countries such as Mali, Burkina Faso, and the Central African Republic. This study revealed that Wagner provides military support to Sahelian governments facing jihadist insurgencies, its operations have been linked to human rights violations, civilian casualties, and further destabilization. Additionally, its engagement often weakens democratic institutions by reinforcing authoritarian rule and reducing Western influence in the region. The group’s involvement in economic sectors, particularly in resource-rich areas, raises concerns over neo-colonial extraction practices and the financing of armed conflicts. The study highlights how Wagner’s activities exacerbate regional security challenges by deepening divisions between local governments and their Western allies, increasing the risks of prolonged conflicts. Moreover while Wagner may provide short-term military advantages to host states, its long-term impact threatens sustainable peace and governance in the Sahel. On the whole, strengthening regional security frameworks, enhancing governance, and promoting multilateral security cooperation are essential to mitigating the destabilizing effects of foreign private military actors.